2006
DOI: 10.1021/ja068271i
|View full text |Cite
|
Sign up to set email alerts
|

Spirastrellolide B Reveals the Absolute Configuration of the Spirastrellolide Macrolide Core

Abstract: The new macrolide spirastrellolide B (5) has been isolated from extracts of the marine sponge Spirastrella coccinea collected in Dominica. Chemical transformations of spirastrellolide B have converted it to a bromine-containing crystalline derivative 8 that has a truncated side chain. Single-crystal X-ray diffraction analysis of the derivative 8 has revealed the absolute configuration of the macrolide core of spirstrellolide B to be 3R,7S,9S,11S,13R,14S,17S,20S,21R, 22S,23S,24S,27R,29S,31R,34S,35R,37S,38S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 6 publications
3
49
0
6
Order By: Relevance
“…Amongst the various possibilities that were contemplated and explored, [13] an alkyl-Suzuki reaction seemed particularly attractive (Scheme 2). [15][16][17][18] This transformation holds the promise of being productive because it allows the critical bond forming event to occur one carbon atom further away from the massive [5,6,6]-bis(spiroacetal) motif. At the same time, it might provide us with the unique opportunity to turn the steric hindrance exerted by the BC and DEF ring systems into a strategic advantage.…”
mentioning
confidence: 99%
“…Amongst the various possibilities that were contemplated and explored, [13] an alkyl-Suzuki reaction seemed particularly attractive (Scheme 2). [15][16][17][18] This transformation holds the promise of being productive because it allows the critical bond forming event to occur one carbon atom further away from the massive [5,6,6]-bis(spiroacetal) motif. At the same time, it might provide us with the unique opportunity to turn the steric hindrance exerted by the BC and DEF ring systems into a strategic advantage.…”
mentioning
confidence: 99%
“…Anhand der in verschiedenen Solventien aufgezeichneten NMR-Spektren, der IR-und Massenspektren, der optischen Drehungen, der CD-Spektren und der HPLC-Retentionszeiten wurde nachgewiesen, dass die synthetische Verbindung mit dem Methylester des Naturstoffs identisch ist; damit wurde zugleich die Strukturbestimmung von Spirastrellolid A bestätigt. [2,11,12] Wir erwähnten zu Beginn das Zusammenspiel von Biologie und Chemie, bei dem ein bestimmter Assay auf Zellbasis zur Entdeckung einer neuen Molekülstruktur, Spirastrellolid A (1), genutzt wurde. Die erfolgreiche Totalsynthese dieses Naturstoffs ist bemerkenswert wegen der Geschwindigkeit, mit der sie angesichts einer Reihe anfänglicher stereochemischer Unsicherheiten gelang.…”
Section: Schema 3 Von Pan Und De Brabanderunclassified
“…Ein Durchbruch bei der Strukturbestimmung der Spirastrellolide gelang 2007 durch die Beschreibung eines kristallinen Derivats des verwandten Naturstoffs Spirastrellolid B durch Andersen et al [11] , die die absolute und relative Konfiguration des makrocyclischen Gerüsts aufdeckte. Ende 2007 [12] [3][4][5] für die Strukturbestimmung von Spirastrellolid A. PMB = para-Methoxybenzyl, TBS = tert-Butyldimethylsilyl, TPS = Triphenylsilyl.…”
unclassified
“…Even though the 1 H signals of H-44, H 2 -45, and H-46 were clearly observed in the methyl ester 4, chemical shifts of 1 H signals in the region between C-2 and C-12 did not perfectly coincide with those in the literature. 2 It was reported that the 1 H NMR spectrum of spirastrellolide F methyl ester exhibited a strikingly dynamic behavior due to the presence of an intricate hydrogen-bonding network, whereas the 13 C chemical shifts did not fluctuate. 6 We therefore considered that the 1 H NMR chemical shift discrepancies observed in our case arose from the different degree of hydrogen-bond formation, which should be concentration-dependent.…”
mentioning
confidence: 99%